Recreational football and bone health: a systematic review and meta-analysis - Milanovic, Z.; Covic, N.; Helge, E. W.; Krustrup, P.; Mohr, M. (Sports Medicine, 2022)
Background: Recreational football is an intense, versatile form of exercise with multiple high- and odd-impact actions. Recreational football is therefore hypothesized to be suitable for bone modeling and bone health. Objective: The aim of the present systematic review and meta-analysis was to evaluate the effects of recreational football on bone mineral density (BMD), bone mineral content (BMC) and bone turnover markers (BTM). Design: Systematic review and meta-analysis. Data Sources: MEDLINE, PubMed, SPORTDiscus, Web of Science, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Google Scholar were searched prior to September 2021. A manual database search was also performed using the following key terms, either singly or in combination: recreational football/soccer, street football/soccer, recreational small-sided games, effect, influence, impact, bone turnover markers, bone mineral density, bone turnover marker, bone health, osteogenesis, CTX, osteocalcin, P1NP. Eligibility Criteria for Selecting Studies: Randomised and matched controlled trials with participants allocated to a recreational football group or any other type of training intervention or passive control group were included. The primary outcome measures were total BMD, lower limb BMD, total BMC, lower limb BMC, osteocalcin, procollagen type 1N-terminal propeptide (P1NP) and collagen type 1 cross-linked C-telopeptide (CTX). A total of 17 papers met the inclusion criteria and were included. Statistical Analysis: Comprehensive Meta-analysis V.2 software (Biostat, Englewood, New Jersey, USA) was used for the meta-analyses. Risk of Bias: Agreement between the two reviewers was assessed using RoB2 tool and k statistics for full-text screening and rating of relevance and risk of bias. The k agreement rate between reviewers was k = 0.92. Results: The football interventions included were based on studies having a duration of 12-64weeks with one 5-year follow-up study and with a training frequency of 1-3 sessions/wk. Training sessions were 45-60min sessions of 3v3 - 7v7 small-sided games. The subjects covered an age span from 9 to 73years. Five studies examined recreational football effects in females, nine studies in males and three studies included both sexes. Recreational football training produced a statistically significant effect (mean difference = 0.02g/cm2, 95% confidence interval: 0.00-0.03, P = 0.02) on lower limb BMD and negligible effects for total BMD compared to no-exercise controls. The recreational football effects on total and lower limb BMC, when compared to both no-exercise controls and exercise controls, were negligible. A moderate to large significant increase in osteocalcin, P1NP and CTX was observed for recreational football compared to both no-exercise controls and exercise controls. Conclusion: In conclusion, recreational football training regimes lasting 12-64weeks have a large osteogenic impact on bone turnover markers in comparison with no-exercise controls as well as exercise controls, and beneficial effects on lower limb BMD compared to no-exercise controls. Short and medium duration recreational football interventions have negligible effects on whole-body BMD and BMC (total and lower limb), with magnitudes similar to those of other exercise modes.